The repertory grid technique in the measurement of images of potential migration destinations: An exploratory application in a rural out migration zone of Colombia - Mackenzie, Hilary J.D (University of Ottawa (Canada), 1977)
Abstract not available.
Keywords: Sociology, Theory and Methods.